The Impact of Participative Management Structures in Improving Employee Participation and Employee Involvement under Conditions of Developing a New Normal in Organisations - X. Tetwa; R. Van Der Walt; L. Bezuidenhoud (Re-engineering Business Processes in the New Normal - The Business and Economic Development Post COVID-19 and the Restructuring of the Global Economy: Proceedings of 8th International Conference on Business and Management Dynamics, 2023)
The Conference theme is spot-on with description of Re-engineering business processes in the new Normal. It is highly unlikely that we will revert directly to Pre-Covid business and management processes. This paper explores how processes can be enhanced by making use of employee participation and employee involvement structures in organisations. Employees are likely to show less resistance to change if an employee participation and employee involvement is used.